FEATURES OF THE IMPLEMENTATION OF INNOVATIVE TECHNOLOGIES IN THE PERSONNEL MANAGEMENT SYSTEM (Economic journal of Lesya Ukrainka Volyn National University, 2025)
Introduction. The article considers new approaches to the study of the feasibility of introducing innovative technologies into the personnel management system. The purpose of the article. The purpose of the article is to analyze innovative methods of personnel management at enterprises, taking into account the specifics of implementation of innovations in management activities, as well as to study foreign experience in the field of personnel management for effective implementation at Ukrainian enterprises.       Methods. The methodological basis for the study of innovative technologies in the personnel management system is the theoretical study of scientific works of researchers on this topic, domestic and foreign experience by the method of analysis and synthesis, to form a holistic view of the personnel management system. In the course of the study, the following theoretical methods were used: comparison and analogy, abstraction and generalization, and a systematic approach, where the personnel management system was studied as an integral system. Our study also used empirical methods of management, such as observation and interviewing, which allowed us to more deeply substantiate the features of the introduction of innovative technologies in the personnel management system      Results. The study resulted in substantiation of the principles of implementation of innovative technologies of the personnel management system at enterprises, practical recommendations for the implementation of innovative technologies in the personnel management system at enterprises The subsystems of personnel management and innovative technologies of personnel management are characterized. The feasibility of using such innovative technologies as personnel leasing, personnel audit and coaching in the field of personnel management is substantiated and it is proposed to introduce these tools into the activities of the enterprise. Conclusions. Successful implementation of innovative technologies in the HR management system requires a comprehensive approach to understanding the formation of strategic goals through training, motivation and readiness for continuous development and transformation. After all, the introduction of innovative technologies into the HR management system is a strategic necessity of today. One of the features of modern organizational activity is that the efficiency of activity and the scale of achievements of the enterprise depend on the level of development of the personnel management system, especially in the field of management. In this context, questions arise regarding the development of personnel and the formation of skills and abilities to assess the activities of personnel and the ability to motivate them. Numerous studies show a direct relationship between motivated personnel and management effectiveness. Therefore, the issue of personnel development through the implementation of innovative technologies in the personnel management system is relevant.
Keywords: personnel, personnel management, innovative technologies of personnel management, personnel management system.